The Role of Digital Leadership, Total Quality Management, and Knowledge Management on Sustainability Management of Vocational Schools - Suharto, Suharto; Siswanto, Edy; Prasetyo, Totok; Sarana, Sarana (Universitas Negeri Semarang, 2023)
The aims of this study is to analyze the relationship digital leadership significantly effects on Sustainability Management, digital leadership on total quality management, digital leadership on knowledge management, total quality management on sustainability management, knowledge management on sustainability management and knowledge management on total quality management. This study uses quantitative research methods. The data sources used in this study are primary and secondary data sources. The main data in this study comes from the results of a questionnaire survey of 320 vocational school teachers determined by simple sampling method. The data analysis method used in this study is structural equation modeling (SEM) which is a descriptive statistical test used to verify hypotheses while verifying their validity and reliability. Data processing was performed using the SmartPLS 3.0 application. Here are the results of this survey: Digital leadership has a great impact on sustainability management Digital leadership has a great impact on total quality management Digital leadership has a great impact on knowledge management Total quality management has a great impact on sustainability management Gives Knowledge management has a huge impact. Impact on Sustainability Management Knowledge management has a significant impact on overall quality management.